Effects of the aqueous extracts of Rhodamnia cinerea on metabolic indices and sorbitol-related complications in Type 2 diabetic rats - Mustapha Umar Imam,; Maznah Ismail,; Sasikala M. Chinnappan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
There is growing interest in the use of plant bioresources for managing Type 2 diabetes. In this study, Rhodamnia cinerea, which is used traditionally to manage diseases in Malaysia, was explored for its antidiabetic effects. Type 2 diabetic rats were managed for 4 weeks using aqueous extract of R. cinerea or quercetin. Weights and fasting glucose were measured weekly, while serum lipid profiles, insulin, antioxidant status, urea, creatinine and liver enzymes were assayed at the end. Sorbitol contents, antioxidant capacities and aldose reductase activities of the kidney, lens and sciatic nerve were also assessed. The results showed that the aqueous extract of R. Cinerea mainly contained Myricitrin and it reduced glycemia (p>0.05), lipid profiles (p<0.05), F2-isoprostanes (p<0.05) and overall metabolic condition of type 2 diabetic rats. R. cinerea also attenuated sorbitol contents of the nerve (p<0.05) and kidney (p<0.05), partly through regulating the activity of aldose reductase (p<0.05 for nerve) and sorbitol dehydrogenase (p<0.05 for kidney) in comparison with diabetic untreated group. Quercetin is a known aldose reductase inhibitor and can improve several metabolic indices related to Type 2 diabetes. In this study, the results of R. cinerea were comparable to or better than those of quercetin, suggesting that R. cinerea extract can be a good candidate for managing Type 2 diabetes and its complications related to sorbitol accumulation.